Budapest karrierje a világ nagyvárosai között - Tóth, József (Közép-Európai Közlemények, 2009)
In the age of globalisation the growth of big cities notably accelerated, and the processes that lead to their functional enrichment, the increase of their versatile importance, and to their emergence from among all the constituents of the settlement system and of the settlement stock, strengthened. After underlining some idiosyncrasies of the theme, it is by all means worth to be analysed from a territorial-structural aspect. In this study we attempt to do this analysis by focusing on the role of Budapest and how it adjusted in time. The altering position of Budapest among metropolises is a result of complicated processes and it cannot be easily gauged as it contains several hardly quantifiable components as well. In our current overview we operate with the most accessible indices of the quantifier aspect; the population size and the city’s position that it takes accordingly. Sometimes the use of this index is not trouble-free as in certain cases our sources are also contradictory. Taking all these into account we attempt to bed the adjustment of Budapest’s position into worldwide and European processes.